Evaluation of bioactive compounds in different extracts of Linum usitatissimum and their antibacterial properties - Fadzir, Ummu Afifah; Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Darnis, Deny Susanti (University Indonesia, 2018)
Antibacterial agents from natural sources have been suggested as alternatives for treating infectious diseases due to their low side effects. Flaxseed (Linum usitatissimum) exhibits some antibacterial properties, but its effects against oral pathogens are poorly understood. This study investigated flaxseed extracts’ antibacterial effects against such pathogens. Methods: Non-polar and polar extracts of flaxseed, with n-hexane, dichloromethane (DCM) and methanol (MeOH), were prepared by sequential Soxhlet extraction. All extracts were qualitatively screened through gas chromatography–mass spectrometry to detect bioactive compounds. Antibacterial activities of flaxseed extracts with different volumes per disc (Oxoid, Badhoevedorp, Netherlands) (5, 7, 10, 12 and 15 μL/disc) were evaluated against four different oral pathogens: Streptococcus pyogenes, Streptococcus mutans, Lactobacillus casei and Enterococcus faecalis, using the disc diffusion method. Flaxseed extracts’ inhibitory activities against the tested oral pathogens were examined by measuring the inhibition zone diameter. Results: Polar extract (methanolic extract) demonstrated significant antibacterial activity (p<0.01) against all tested oral pathogens, with inhibition zones comparable to those for penicillin. In contrast, n- hexane and DCM extracts demonstrated variable antibacterial activities. Conclusions: This study suggests that Linum usitatissimum methanolic extract exhibited the best inhibitory activity on all tested strains compared to the other extracts.